Relationship Between Pregnancy Anemia and Depression in Postpartum Mothers: Systematic Review - Wijayanti, Poppy; Bainuan, Lina Darmayanti; Yuliana, Nur Aida (Journal of Maternal and Child Health, 2024)
Background: Anemia is one of the most significant global public health problems that affects a person's physical and mental abilities. Geography, lifestyle, and diet influence the prevalence of anemia in pregnant women, which is estimated to range from 14 to 80% in different countries (WHO, 2019. This study aims to analyze the relationship between pregnancy anemia and the incidence of depression in postpartum mothers. Subjects and Method: Systematic Review using the PRISMA diagram in the RevMan 5.3 application. Database searches from PubMed, Scopus, Wiley Online Library, and Science Direct were conducted in 2022-2024, and can be accessed for free, with the search terms "Anemia in pregnancy" OR "Low level of hemoglobin in pregnancy" AND "depression". Results: A total of 6 articles that were selected from 432 quantitative articles based on inclusion and exclusion criteria, showed that there was a significant relationship between gestational anemia and the incidence of depression in postpartum mothers. However, some articles have not shown a significant association between pregnancy anemia and postpartum depression. Conclusion: Although there are studies that have not significant results, the administration of blood supplement tablets and monitoring of Fe intake in pregnant women for the prevention of anemia is important because there is a 50% chance of causing depression and other consequences during and after childbirth.